2010
DOI: 10.1002/mnfr.200900189
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma n‐3 polyunsaturated fatty acid is associated with improved insulin sensitivity in type 2 diabetes in China

Abstract: Increased tissue n-3 polyunsaturated fatty acid (PUFA) is associated with improved insulin sensitivity in type 2 diabetes. However, this relationship among Chinese is not clear. To investigate the relationship between plasma phospholipids (PL) fatty acid composition and insulin resistance (IR) in type 2 diabetes mellitus, 186 type 2 diabetes and 180 healthy subjects were studied in this case-control study. In the sex, age and BMI controlled partial correlation, homeostasis model assessment (HOMA)-IR and blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 47 publications
3
25
2
Order By: Relevance
“…Also in this case our results are in contrast with Simão et al that reported an increase of insulin resistance with n-3 PUFA, but in line with Thorseng et al [44] and Huang et al [45] that suggested that some types of n-3 PUFA may have a protective effect against insulin resistance. Also a review conducted by Moreno-Aliaga et al [46] reached the same results, concluding that the ability of n-3 PUFA to improve obesity and insulin resistance conditions partially results from the modulation of white adipose tissue metabolism and the secretion of bioactive adipokines including leptin, ADN, and visfatin.…”
Section: Discussioncontrasting
confidence: 67%
“…Also in this case our results are in contrast with Simão et al that reported an increase of insulin resistance with n-3 PUFA, but in line with Thorseng et al [44] and Huang et al [45] that suggested that some types of n-3 PUFA may have a protective effect against insulin resistance. Also a review conducted by Moreno-Aliaga et al [46] reached the same results, concluding that the ability of n-3 PUFA to improve obesity and insulin resistance conditions partially results from the modulation of white adipose tissue metabolism and the secretion of bioactive adipokines including leptin, ADN, and visfatin.…”
Section: Discussioncontrasting
confidence: 67%
“…Higher D6D activity could contribute to the high proportion of 18:3n6 in patients with type 2 diabetes in the present study, but 18:2n6 levels were higher in patients with type 2 diabetes than in the controls [29]. Huang et al [27] also observed that plasma levels of n-6 PUFA and 18:2n6 were higher in Chinese patients with type 2 diabetes than in the controls, and positively correlated with glucose levels. The situation is complicated regarding 20:4n6; both deleterious and protective effects of 20:4n6 have been reported [30].…”
Section: Discussionmentioning
confidence: 57%
“…Djoussé et al [10] found no association between plasma levels of n-3 PUFAs and the incidence of type 2 diabetes, but did observe a lower risk of type 2 diabetes in participants who were in the highest quartile of 22:5n3 and 22:6n3 plasma concentrations, suggesting that at certain levels, n-3 PUFA might reduce the risk of type 2 diabetes. Blood levels of 22:5n3 and 22:6n3 were 10% higher in the present study when compared to Western populations, and 8% higher than in Western populations in a Chinese study [27]. …”
Section: Discussionmentioning
confidence: 99%
“…In the Shanghai Women's Health Study, a higher intake of long-chain n-3 fatty acids was associated with a lower risk of T2D in a population of 64,193 Chinese women [24]. Plasma n-3 long-chain fatty acids were associated with improved insulin sensitivity in Chinese T2D patients [25]. Our present study supports that a higher level of n-3 fatty acids was associated with a lower risk of T2D, and a higher level of n-3 fatty acids was also able to modify the genetic risk of T2D.…”
Section: Discussionmentioning
confidence: 99%